Adolescents Who Are Violent Toward Their Parents: An Approach to the Situation in Chile - Ilabaca Baeza, Paola Andrea (Journal of interpersonal violence, 2021)
Child-to-parent violence has been defined as any act used by children to gain power and control by generating fear in their parents and that seeks to cause physical, psychological, and/or financial harm to their parents. This behavior puts family safety at risk due to the imbalance of power that it generates. For this reason, most abused parents feel guilty and humiliated. Child-to-parent violence has been historically underresearched compared with other studies about family violence. Most of the research conducted on this topic has been carried out in Europe and North America in the least decades. Nevertheless, in Chile, the research about child-to-parent violence has been really insufficient. This article presents the first analysis conducted in Chile regarding the prevalence of violent adolescent behavior toward parents. A total of 1,861 adolescents between the ages of 13 and 20 (M = 16.1, SD = 1.29) participated in the study (48.1% boys; 51.9% girls). Participants answered an ad hoc questionnaire on child-to-parent violence. Our findings indicate that psychological, economic, and physical aggression against the mother was more frequent than against the father. Daughters are more likely to use psychological aggression toward their fathers and mothers, whereas sons are more likely to use financial and physical aggression. Young people living in single-parent families are more likely to use financial and psychological aggression toward their mother. These findings reveal the impact of gender and family structure on aggression toward parents.